IMPLEMENTASI PEMBELAJARAN BERBASIS IQRA’ DI SEKOLAH (Upaya Menerapkan Pembelajaran Berbasis Higher Thinking Order Skills) - Ade Suhendra; Irwan Saleh Dalimunthe; Muhlison Muhlison (IAIN Padangsidimpuan, 2020)
Learning-based Iqra’ is learning that’s Iqra’ made as one of the focus on learning. Learning-based Iqra’ is one of the solutions that’s given us the answer to problems in our society now. This paper describes reading as a part of the integration of the learning process to produce a generation that has a good competence of literacy.